2008
DOI: 10.2337/dc07-0912
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Indices, Health Behaviors, and Incidence of Diabetes in Australia

Abstract: OBJECTIVE -This national, population-based study reports diabetes incidence based on oral glucose tolerance tests (OGTTs) and identifies risk factors for diabetes in Australians.RESEARCH DESIGN AND METHODS -The Australian Diabetes, Obesity and Lifestyle Study followed-up 5,842 participants over 5 years. Normal glycemia, impaired fasting glucose (IFG), impaired glucose tolerance (IGT), and diabetes were defined using World Health Organization criteria.RESULTS -Age-standardized annual incidence of diabetes for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
199
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(229 citation statements)
references
References 32 publications
27
199
2
1
Order By: Relevance
“…This discordance between indices of glucose metabolism has been observed by others, 1,4,12 is well documented in the able-bodied population, 13,14 and is likely because of the different metabolic determinants underlying impaired fasting glycemia and IGT. That is, IGT is thought to reflect peripheral insulin resistance, predominantly within skeletal muscle, whereas impaired fasting glycemia is thought to reflect hepatic insulin resistance and b-cell deficiency.…”
Section: Discussionsupporting
confidence: 56%
“…This discordance between indices of glucose metabolism has been observed by others, 1,4,12 is well documented in the able-bodied population, 13,14 and is likely because of the different metabolic determinants underlying impaired fasting glycemia and IGT. That is, IGT is thought to reflect peripheral insulin resistance, predominantly within skeletal muscle, whereas impaired fasting glycemia is thought to reflect hepatic insulin resistance and b-cell deficiency.…”
Section: Discussionsupporting
confidence: 56%
“…These low response rates and high loss to follow-up may mean that the proportion of people who underwent WC gain is not wholly reflective of the population incidence rates (16) . The low response rates could lead to either an under-or overestimation of weight gain (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Plasma diabetes status was determined by a blood sample undertaken during the physical examination (16) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective studies have shown that increased levels of physical activity can reduce progression to diabetes [5,6]. Recent population-based studies have examined the relationship between physical activity and overall progression to diabetes [7][8][9]. Most studies have classified physical activity into a two or three category variable not analysing dose-response relationships and not focusing on different types of physical activity (leisure, commuting and occupational) [10].…”
Section: Introductionmentioning
confidence: 99%